Paradigma Ilmu Integralistik dalam Pemikiran Kuntowijoyo: Integralisasi dan Objektifikasi Islam - Dendi, Dendi Nugraha; Aska, Muhammad Aska Irfani; Afdalul Ummah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The concept of Islamic science initiated by Kuntowijoyo aims to integrate Islamic values ​​with modern science to answer contemporary social and intellectual challenges. This study uses a literature method with a qualitative approach, focusing on the analysis of Kuntowijoyo's main work, Islam as Science, and other supporting sources. The results of the study indicate that Islamic science offers two main steps, namely integral: the integration of revelation and reason, and the objectification of science to provide universal benefits. In addition, the concept of prophetic social science that he developed emphasizes the values ​​of humanization, liberation, and transcendence as the basis for social transformation oriented toward justice and morality. With this paradigm, Islamic science not only bridges the dichotomy between religious science and general science but also builds a scientific framework that is intellectually and spiritually relevant to face the challenges of modernity.